Pembinaan Keagamaan Masyarakat di Kabupaten Bone Melalui Program KKN Mahasiswi STIBA Makassar - Hijrayanti Sari; A. Hawariah (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
The implementation of The Real Work Lecture (KKN) of students of Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar aims to take a role in helping the Government of Bone Regency of South Sulawesi Province in realizing the mission of mental and spiritual development between religious people and carrying out tri dharma higher education on the pillars of community service. The method of implementing the KKN program begins by observing the condition of the community using SOAR analysis. The work program is carried out both online and offline. Online activities include Taklim Fikih Wanita Pekanan and Kajian Muslimah with the target of Muslim women with a younger age and have the ability to access activities. While offline activities include Bimbingan Islam Intensif and Dirosa with the target of mothers who are unable to access activities through online. The enthusiasm of the community from all activities that have been carried out is quite large and becomes a recommendation so that there are still continued activities for the establishment of built areas.